Correction: Liposomes loading sodium chloride as effective thermo-seeds for microwave ablation of hepatocellular carcinoma. Issue 44 (7th November 2018) - Zhou, Qunfang; Wu, Songsong; Gong, Ningqiang; Li, Xin; Dou, Jianping; Mu, Mengjuan; Yu, Xiaoling; Yu, Jie; Liang, Ping
Abstract : Correction for 'Liposomes loading sodium chloride as effective thermo-seeds for microwave ablation of hepatocellular carcinoma' by Jie Yu, Ping Liang et al., Nanoscale, 2017, 9, 11068–11076.